Probability of Hypertension in Advancing Ages of Women - Fajar Awalia Yulianto; Nurul Romadhona; Febyana Rosarianto; Vihannis Rahmanda; Salman Barlian; Tresya Anggi Tania; Romy Reynaldi Gunawan; Sumayya Nuri Fuadana Aulia Ul Haque; Rifa Nataputri; Aulia Nur Amalia; Paulina Maresta; Haris Nugroho (Global Medical & Health Communication (GMHC), 2020)
Hypertension is a problem in Indonesia, with 34.1% prevalence. The number reflected the number of hypertensive patients in the 2016 clinic report of Pasirjambu Public Health Center as the most prominent non-communicable disease. This research aimed to discover the specific age of onset and risk factors of hypertension in the village where the health center located. A rapid survey collected the data in May 2017, where 210 women (representing their household) were chosen by randomization inside their respective clusters. Risk factors were analyzed by a robust and parsimonious logistic regression model along with probability count on age as the final prediction. The prevalence of hypertension was 59.5% (95%CI=52.9, 66.2%). Risk factors for hypertension were age (OR=1.06, p=0.00), stress (OR=1.74, p=0.09) and family history (OR=1.99, p=0.03) but the protective factor was consumption frequency of salty food (OR=0.64, p=0.10). In conclusion, a woman would have a 42.9% chance (95%CI=33.7, 52.1%) for having hypertension at 40 years old of age after adjusted by other risk factors. Despite only two modifiable risk factors that can be intervened with, it would be worth trying to decrease the pace of onset in hypertension and the prevalence. KEMUNGKINAN HIPERTENSI BERDASAR ATAS USIA PADA WANITAHipertensi merupakan sebuah masalah di Indonesia dengan prevalensi sebesar 34,1%, angka tersebut terlihat dalam laporan tahunan Puskesmas Pasirjambu sebagai penyakit tidak menular terbanyak di wilayah kerjanya. Tujuan penelitian ini adalah mengetahui usia munculnya hipertensi dan faktor risikonya. Pengumpulan data dilakukan melalui survei cepat di bulan Mei 2017, melibatkan 210 wanita yang mewakili  rumah tangganya dipilih secara random. Faktor risiko dianalisis menggunakan regresi logistik dengan hasil akhir berupa prediksi kemungkinan. Hasil penelitian menunjukkan prevalensi hipertensi sebesar 59,5% (IK95%=52,9; 66,2%). Usia (OR=1,06; p=0,00), stres (OR=1,74; p=0,09) dan riwayat hipertensi dalam keluarga (OR=1,99; p=0,03) menjadi faktor risiko, sedangkan frekuensi konsumsi makanan asin (OR=0,64; p=0,10) menjadi faktor protektif. Setelah adjusted terhadap variabel lain, kemungkinan untuk hipertensi seorang wanita usia 40 tahun sebesar 42,9% (IK95%=33,7; 52,1%). Pencegahan untuk menurunkan prevalensi dan laju insidensi dapat dilakukan pada usia tersebut walaupun hanya ada dua faktor risiko yang dapat dimodifikasi.